ECONOMIC BEHAVIOR OF MICRO AND SMALL BUSINESS HOUSEHOLDS IN A BRANCHLESS BANKING SYSTEM - Ktut Silvanita Mangani; Yusman Syaukat; Bustanul Arifin; Mangara Tambunan (Faculty of Economics and Business, Universitas Gadjah Mada, 2019)
Introduction: This study aims to analyze how the existence of branchless banking in rural areas affects the economic behavior of the micro and small business households, and vice versa. Background Problem: Within the framework at inclusive finance program, Indonesia has implemented the branchless banking model. However, the impact of the branchless banking system to micro and small business household has not discussed yet. Research Method: The research was conducted in Bogor District, with many remote villages adjacent to Jakarta, a capital city of Indonesia. A total of 97 samples of micro and small business households were selected from 13 sub-districts. The estimation was conducted using 2SLS method. The model describes the existing condition that explains the uniqueness of the economic behavior of the micro and small business households in a branchless banking system. Novelty: Studies related to branchless banking generally analyzed from the perspective of banking institutions. However, this study focusses on supply side, namely it analyzDe the household economic behavior using simultaneously equation model. Findings: The results show that the presence of branchless banking agents, as measured by the value of the transactions conducted by the households, have little effect on the economic behavior of the micro and small business households. On the other hand, the economic behavior variables which are expected to affect the value of the transactions do not occur. The results explain that the utilization of the banking services provided through agents in the branchless banking system is in the form of payment transactions. In addition, the presence of branchless banking in rural areas has not affected production activities and vice versa. Conclusion: This study suggests a further study to find out the factors that make business actors unwilling to perform financial transactions related to their production activities through branchless banking agents.